2016
DOI: 10.3906/biy-1501-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification and prediction of the consequences of nonsynonymous SNPs in glyceraldehyde 3-phosphate dehydrogenase (GAPDH) gene of zebrafish Danio rerio

Abstract: The recent progress in DNA sequencing and computational algorithms dramatically heightened the value of single nucleotide polymorphism (SNP) databases. The experimental studies of mutation for the particular gene of interest are laborious and timeconsuming. In this study, we used several computational algorithms to investigate the structural and functional consequences of SNPs on the glyceraldehyde 3-phosphate dehydrogenase (GAPDH) gene of zebrafish (Danio rerio). The GAPDH gene is involved in multiple cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Extracted RNAs were verified by PCR using β - actin house-keeping gene primers. Genomic DNA was isolated from the liver of rohu via the phenol-chloroform extraction method [ 30 – 32 ]. The quantity and quality of extracted total RNA and genomic DNA were determined by agarose gel electrophoresis and Nanodrop readings.…”
Section: Methodsmentioning
confidence: 99%
“…Extracted RNAs were verified by PCR using β - actin house-keeping gene primers. Genomic DNA was isolated from the liver of rohu via the phenol-chloroform extraction method [ 30 – 32 ]. The quantity and quality of extracted total RNA and genomic DNA were determined by agarose gel electrophoresis and Nanodrop readings.…”
Section: Methodsmentioning
confidence: 99%
“…The earlier studies reported that SIFT, I‐Mutant, PROVEAN and PANTHER algorithms were used for investigating the effect of non‐synonymous mutation (Rasal et al, 2017). In zebrafish and farmed rohu, impact of nsSNPs were analysed in different key genes such as GAPDH (Rasal et al, 2015), TLR22 (Chakrapani et al, 2018) and MSTN (Rasal et al, 2016a) using computational tools. Thus, recently generated genomic data and SNPs in rohu will be utilized for predicting structural and functional impact of missense variants on protein structure and functions.…”
Section: Molecular and Genomics Techniquesmentioning
confidence: 99%
“…Direct experimental studies linked to incorporating mutation in a particular gene of interests have been laborious and time-consuming. The computational study can efficiently produce useful information to rationalize and guide in undertaking further experimental studies [ 28 30 ]. These point mutations affect gene expressions and their products by altering change in their functional activities [ 31 ].…”
Section: Introductionmentioning
confidence: 99%